(untitled) (College of Basic Education Research Journal, 2025)
In this paper, Banach contraction method was used to solve linear and nonlinear partial integra differential equations of Volterra type and compared them with exact solutions to demonstrate accuracy of the proposed method. Results revealed that Banach contraction method is very effective, simple and of a high accuracy to solve higher order Integro -differential equations. Four different examples were solved and compared with exact solutions using mean squared error and absolute error. The tables and figures show convergence of proposed method in solution.